A review of the taxonomy and taxonomic characters of Philippine Alocasia (Schott) G. Don (Araceae) - Medecilo, Melanie P. (Animo Repository, 2013)
This study was conducted to provide insights in the taxonomy of Philippine Alocasia by investigating the morphology, anatomy and pollen characters of the component species. Results showed that morphological characters can be used to a certain extent in delimiting taxa, while leaf anatomical characters showed continuous variation between species and are not of much use for taxonomic recognition when used alone. The combined morphology, anatomy and pollen characters showed a clear distinction on the 'heterophylla', 'longiloba', 'macrorrhizos', 'odora', 'princeps' and 'scabriuscula' groups, which agree with the classification of Alocasia proposed by Hay in 1991, 1998, 1999. The distribution and ecology of the species were also reported. The center of diversity of Alocasia in the Philippine archipelago is in Luzon and the Visayan regions. All of the species, except A. macrorrhizos, are endemic to the country. This study shows that the Philippines now ranks second, next to Borneo, in terms of species diversity of Alocasia.